Sulfiredoxin may promote metastasis and invasion of cervical squamous cell carcinoma by epithelial–mesenchymal transition - Xiaoyan Chen; Kangyun Lan; Qin Liu; Xue Yang; Hui Wang (Tumor Biology)
Sulfiredoxin (Srx), a novel oxidative stress-induced antioxidant protein, has been reported to be expressed in several human tumour tissues. However, the expression and functions of Srx in cervical squamous cell carcinoma remain unknown. Here, we proved that expression of Srx was upregulated in cervical tissues as revealed by immunohistochemistry, and revealed a close correlation between the protein’s expression and the expression level of one core epithelial–mesenchymal transition marker, E-cadherin. We demonstrated that Srx was overexpressed in cervical squamous cell carcinoma and its expression level was closely correlated with lymph node metastasis and invasion of cervical squamous cell carcinoma. Meanwhile, Srx expression was negatively correlated with E-cadherin expression. The remission time (tumour-free status after surgery) of the Srx strong staining group was significantly shorter than that of the Srx weak staining group. We silenced Srx by short hairpin RNA in HeLa and SiHa cells. Diminished Srx expression upregulated E-cadherin expression. The cell invasion and migration activity in the ShSrx group were obviously decreased in HeLa and SiHa cells. Moreover, Srx regulated the expression of the other marker of epithelial–mesenchymal transition, vimentin. In conclusion, the study suggested that Srx was highly expressed in cervical squamous cell carcinoma and may promote invasion and metastasis of cervical squamous cell carcinoma via regulating epithelial–mesenchymal transition.